EVOLUTION OF THE NOTION AND THE KEY CONCEPTS OF ELITE - Кашаба, О.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The genesis and evolution of the notion of ‘elite’ are analyzed, the basic concepts of elites are examined. Despite the diversity of scientific theories most authors tend to assume elite as a privileged layer of the population, a minority that controls the political organization of society, takes part in making decisions and implementation of policy decisions, and by its position and functions is dominant.